2009
DOI: 10.1093/ndt/gfp144
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet and achievement of the NKF/K-DOQITM recommended target values for bone and mineral metabolism in real-world clinical practice--the ECHO observational study

Abstract: This analysis of current European clinical practice shows that-consistent with findings from randomized controlled trials and retrospective observational studies-cinacalcet improves attainment of KDOQI bone metabolism targets in dialysis patients with various stages of SHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
97
1
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 19 publications
11
97
1
11
Order By: Relevance
“…A similar response was observed in patients who were treated with PD and HD; 65% of patients in both groups experienced ≥30% reductions in iPTH levels with cinacalcet therapy. Similar efficacy in PD patients was demonstrated by Urena et al [21].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A similar response was observed in patients who were treated with PD and HD; 65% of patients in both groups experienced ≥30% reductions in iPTH levels with cinacalcet therapy. Similar efficacy in PD patients was demonstrated by Urena et al [21].…”
Section: Discussionsupporting
confidence: 85%
“…There have been numerous studies which have shown reduction of serum intact PTH with cinacalcet in patients on hemodialysis [19][20][21][22][23]. In the first large randomised controlled study (RCT) with 741 patients on maintenance dialysis and secondary HPT, Geofry et al in 2004 concluded that cinacalcet significantly reduces iPTH in patients with CKD-5D versus control [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined results of RCTs and phase 4 studies confirmed these results (11,13,21,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)) (Table1), among other benefits, including a substantial reduction of the elevated bone formation rate/tissue area, generally improving bone disease (57,58). Importantly, two recent prospective RCTs evaluated both the efficacy of cinacalcet in preventing the progression of CV calcifications (ADVANCE) (11), and its effect on clinical outcomes, including all-cause mortality and CV events (EVOLVE) (13).…”
Section: Cinacalcet Use In Patients With Ckd Treated By Dialysismentioning
confidence: 54%
“…5,6 Until 2008, most of the published studies of cinacalcet in dialysis patients, included a small number of peritoneal dialysis (PD) patients. 7,8 A Spanish one-center observational prospective study of 18 patients under PD published in 2008, proved that the use of cinacalcet in PD patients with SHPT resistant to conventional treatment has resulted effective and safe and has improved compliance objectives of the guidelines. 9 This results were corroborated in 2012, in a Spanish multicenter observational prospective study of 54 PD patients.…”
Section: Introductionmentioning
confidence: 99%